Transhumanism in the light of philosophical anthropology - Natucci Cortazzo, Julián P. (Logos. Anales del Seminario de Metafísica, 2020)
The purpose of this article is to show some ideological aspects of the conception of technology and the human being that underlie transhumanism. It attempts to demonstrate these aspects in the light of the philosophical anthropology of Scheler, Plessner and other authors through the following arguments: the criticism of the neutral conception of technology, the rejection of the idea of the human being as homo faber and the transhumanist misunderstanding of life and death. From a discussion of transhumanism with philosophical anthropology it is verified that there is no change of paradigm within it; the old conceptions of the human being, that had been defended by Modernity, are still present.